Retrobulbar blood flow and carotid intima–media thickness alteration may relate to subclinic atherosclerosis in patients with chronic inflammatory diseases. (9th August 2015) - Keles, Nursen; Caliskan, Mustafa; Aksu, Feyza Ulusoy; Keles, Necibe Nur; Karagoz, Vildan; Tekin, Ahmet Selami; Akcakoyun, Mustafa; Kostek, Osman; Elcioglu, Omer; Aung, Soe Moe; Bakan, Ali; Odabas, Ali Riza
Abstract: Objective : AA amyloidosis occurs in the setting of longstanding inflammation. An increased incidence of coronary artery disease (CAD) was noted in patients with chronic inflammatory disease (CID). Retrobulbar blood flow predicts future macrovascular events including CAD. Increase in carotid artery intima–media thickness is regarded as a marker for early atherosclerosis. The relationship between chronic inflammation and atherosclerosis is well known; however, the connection between amyloidosis-advanced CIDs and retrobulbar microvascular function and carotid intima–media thickness (CIMT) is unidentified. We aimed to investigate whether retrobulbar microcirculation and CIMT were impaired or not in amyloidosis-advanced CID patients compared to normal subjects. Methods : Fourteen patients with renal AA amyloidosis and a group of healthy volunteers were included in the study. Measurement of CIMT and retrobulbar blood flow velocities was performed with ultrasound scanner and color Doppler ultrasonography. Results : The CIMT of patients with renal amyloidosis was significantly thicker than that of the normal population ( p  < 0.001). The resistivity index of the ophthalmic artery (OA) of patients with renal amyloidosis was significantly higher than the study group ( p  < 0.001). Conclusion : This study demonstrates that accelerated atherosclerosis which can be shown by increased OA resistivity index and CIMT are found in amyloidal-related CID patients.